The Effect Green Marketing Mix on Corporate Image as Well as Implication for Purchase Intention of Food and Beverages Companies In Indonesia - Ryan Johan Sembiring (Syntax Corporation Indonesia, 2021)
This study aims to analyze and prove effect of the green marketing-based marketing mix consisting of (green product, green price, green distribution, green promotion) on corporate image and its implications for the purchase intention of food and beverage companies in Indonesia, partially or jointly and the effect of the green marketing-minded marketing mix consisting of (green product, green price, green distribution, green promotion) and corporate image on the purchase intention of food and beverage companies in Indonesia, both partially or collectively. The research method used in this research is descriptive and verification methods with a sample of 205 respondents, and the data analysis method used is SEM (Structural Equation Modeling) using the Lisrel Program. Based on the research results, the following findings were found as green product, green price, green distribution and green promotion both partially and collectively have a positive and significant effect on corporate image with a coefficient of determination (R2) of 88%. Likewise, green product, green price, green distribution, green promotion and corporate image either partially or collectively have a positive and significant effect on purchase intention with a coefficient of determination (R2) of 98%. This research finds and proves that to increase purchase intention it is necessary to increase the marketing mix with a marketing perspective (green product, green price, green distribution and green promotion) and corporate image in the non-physical identity dimensions needs to be improved.